2016
DOI: 10.18517/ijaseit.6.6.1373
|View full text |Cite
|
Sign up to set email alerts
|

Client’s Readiness Assessment Success Factors for Outsourcing Software Projects

Abstract: IT services such as software development, application maintenance, disaster recovery, help desk, network, and operations are critical and highly demanded to better support the operations and management of organizations, especially in the government sector. The government sector faces various problems in providing IT services due to constraints or lack of knowledge, skills, and expertise, human resource and technology. Thus, IT services need to be outsourced to overcome these problems. While the need for outsou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The artefact produced in this work is the engineering framework of services computing systems. The evaluation provides important feedback to the framework development [28]. A practical evaluation methodology is used to evaluate the proposed framework based on the experiences of the systems engineers after using the framework.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artefact produced in this work is the engineering framework of services computing systems. The evaluation provides important feedback to the framework development [28]. A practical evaluation methodology is used to evaluate the proposed framework based on the experiences of the systems engineers after using the framework.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the implementation of the systems must be able to provide service values to the organization [28]. The second perspective takes the view of systems engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Cost is one of the key factors under project constraints [138]. When prioritizing certain requirements, the implementation cost should be considered [105], [139].…”
Section: ) Costmentioning
confidence: 99%
“…Therefore, many companies have started to shift to so-called Agile methods to develop such systems [3], and it has been found that the extent of the organizational team's skills [1], [4], [5], culture of the organization [2], [4], nature of project [5], and project constraints [5] must be given in-depth consideration [6] when selecting an Agile method. However, selecting the most appropriate Agile method for a project based on organizational capabilities is a difficult task [7], [8] because there are many Agile methods to choose from, such as Extreme Programming (XP) [9], [10], SCRUM [11], TestDriven Development (TDD) [12], Feature-Driven Development (FDD) [13], Lean Development (LD) [14], Adaptive Software Development (ASD) [15], Agile Modelling (AM) [16], Crystal Family Group (Clear, Red, Orange, Yellow) [17], Internet Speed Development (ISD) [18], [19], Disciplined Agile Delivery (DAD) [6], Agile Software Process Development [20], DevOps [21], Kanban [22] and the Dynamic Systems Development Method (DSDM) [23].…”
Section: Introductionmentioning
confidence: 99%
“…The merging of diverse practices from different Agile methods takes into account diverse factors [25]. Further, management of the project is a concern to all members of the team in assuring successful software projects [26], and this applies to any organization. Relevantly, methods such as Kanban and Scrum prove their suitability in the successful development of projects and their management as well [27].…”
Section: Introductionmentioning
confidence: 99%